2007
DOI: 10.1183/09031936.00083507
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and airflow obstruction: evidence from the PLATINO study in Latin America

Abstract: The aim of the present study was to evaluate the association between history of tuberculosis and airflow obstruction.A population-based, multicentre study was carried out and included 5,571 subjects aged o40 yrs living in one of five Latin American metropolitan areas: Sao Paulo (Brazil); Montevideo (Uruguay); Mexico City (Mexico); Santiago (Chile); and Caracas (Venezuela). Subjects performed pre-and post-bronchodilator spirometry and were asked whether they had ever been diagnosed with tuberculosis by a physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
185
1
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(208 citation statements)
references
References 25 publications
7
185
1
15
Order By: Relevance
“…10 A history of pulmonary TB increased the risk of COPD about 4-fold in men and nearly 2-fold in women, even after adjustment for age, gender, education, ethnic origin, smoking status, exposure to dust and smoke, and respiratory morbidity in childhood. 11 As pulmonary TB remains a common disease in Hong Kong, it may be a significant contributor to airflow obstruction in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…10 A history of pulmonary TB increased the risk of COPD about 4-fold in men and nearly 2-fold in women, even after adjustment for age, gender, education, ethnic origin, smoking status, exposure to dust and smoke, and respiratory morbidity in childhood. 11 As pulmonary TB remains a common disease in Hong Kong, it may be a significant contributor to airflow obstruction in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…[2] In a number of large population-based cross-sectional studies, PTB has also been shown to be strongly associated with the presence of chronic airflow limitation (CAL). [3][4][5][6] In some studies, this association is almost as strong as that for cigarette smoking. [5][6][7] In a community-based study performed in South Africa (SA), 49.2% of adults aged ≥40 years who reported a history of PTB had evidence of CAL (Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 1 or higher).…”
Section: Researchmentioning
confidence: 95%
“…Estos hallazgos, que relacionan la existencia de enfermedad obstructiva de la vía aérea por espirometría en pacientes con secuelas de tuberculosis pulmonar están de acuerdo con lo descrito previamente en otros estudios. (4,5,8,17,19,21,23,24,26,27).…”
Section: Discussionunclassified